Virtue ethics in social work practice - Hugman, Richard, 1954-; Anscombe, A. W.; Pawar, Manohar S.; Wheeler, Amelia (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Using evidence from research with practitioners, integrated with wider material about virtue ethics in the helping professions, this book explores important types of virtue that are central to developing and sustaining good social work Comprised of ten chapters and drawing on extensive research with social workers, as well as wider debates and analysis, the discussion carefully concentrates on everyday experiences and achievements. This approach enables the book to avoid an idealized and prescriptive approach by making clear that virtues vary between contexts and individuals, while at the same time clearly marking out qualities and characteristics of social work that are foundational to the development of practitioners and of the profession as a whole. It will be required reading for students on all BSc/BSW and MSc/MSW courses on professional ethics or preparation for practice"--
OCLC-licensed vendor bibliographic record.
Keywords: Social service -- Moral and ethical aspects; Social workers -- Professional ethics; SOCIAL SCIENCE / Human Services; PHILOSOPHY / Ethics & Moral Philosophy